(untitled) - Vince, Russ (London, 2004)
This book highlights and develops an important conceptual and practical shift in the study of human resource development. The author argues for an organisational understanding of HRD both in theory and in practice.
Keywords: Organizational learning,Organizational learning,Knowledge management; Management